Complete chemistry for cambridge IGCSE [electronic resource] - 349109 Gallagher, RoseMarie author; Ingram, Paul author (New York : Oxford University Press, 2011)
This book meets the needs of all students following the Cambridge IGCSE syllabus for Chemistry. Updated for the most recent syllabus and the latest scientific developments, it covers all aspects of the syllabus content in an attractive and engaging format for both native and non-native speakers of English. Each book is accompanied by a free CD which provides a wealth of support for students, such as practical investigations, practice exam-questions and revision tips. An accompanying Teacher's Guide and Revision Guide are also available. Fully endorsed by Cambridge International Examinations.